2003
DOI: 10.1128/aac.47.5.1739-1741.2003
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia Is Highly Resistant to Human Beta-Defensin 3

Abstract: The bactericidal activity of the novel beta-defensin hBD-3 against 28 species and 55 strains of gram-positive cocci and gram-negative fermentative and nonfermentative rods was tested. All strains proved to be highly or intermediately susceptible to hBD-3 (minimal bactericidal concentration [MBC], <50 g/ml), except for Burkholderia cepacia, for all 23 tested strains of which MBCs were >100 g/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 27 publications
5
58
3
Order By: Relevance
“…Since previous studies have demonstrated that Burkholderia species are very resistant to b-defensins and other antimicrobial peptides (Baird et al, 1999;Burtnick & Woods, 1999;Loutet et al, 2006;Sahly et al, 2003), it is possible that mutations in zmpA and/or zmpB are insufficient to result in increased susceptibility to the antimicrobial activity of these defensins, due to myriad resistance mechanisms. It is also possible that the cleavage products generated by ZmpA or ZmpB retain antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Since previous studies have demonstrated that Burkholderia species are very resistant to b-defensins and other antimicrobial peptides (Baird et al, 1999;Burtnick & Woods, 1999;Loutet et al, 2006;Sahly et al, 2003), it is possible that mutations in zmpA and/or zmpB are insufficient to result in increased susceptibility to the antimicrobial activity of these defensins, due to myriad resistance mechanisms. It is also possible that the cleavage products generated by ZmpA or ZmpB retain antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Determination of Antimicrobial Activity and Salt ToleranceThe antimicrobial activity of theromacin and neuromacin was investigated as described previously (22). Hydramacin-1 4 served as reference molecule and was also measured in parallel.…”
Section: Methodsmentioning
confidence: 99%
“…Arbitrarily, a strain was defined as susceptible to a peptide if it had an MBC or LD 90 of Յ12.5 g/ml, as intermediately susceptible if it had an MBC or LD 90 of Ͼ12.5-100 g/ml, or as resistant if it had an MBC or LD 90 of Ͼ100 g/ml as described elsewhere (22).…”
Section: Methodsmentioning
confidence: 99%
“…Li et al, showed that exposure to sub-inhibitory concentra-287 tions of hBD-3 resulted in a significant upregulation of the expression of the dlt operon, and a 288 subsequent increase in D-alanylation of teichoic acids in S. epidermidis [30]. A comparable 289 mechanism with a change in the bacterial surface charge to resist human beta-defensins is 290 also discussed for Gram-negative bacteria [31]. Therefore, a correlation between the mecha 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Reichel et al Bacterial response to human β-Defensin-3 after chlorhexidine exposure 15 nism of bacteria to circumvent the natural host defence of the skin caused by AMPs and the 292 mechanism for resistance to cationic antimicrobials, e.g.…”
mentioning
confidence: 98%